Ashabul Furudh and Waqf Integration in Contemporary Islamic Wealth Distribution: Revisiting Classical Fiqh in the Indonesia Context - Auliya Yulanda; Irpan Maulana; Ninda Ayu Ijun Husada (Mir'ah: Family Law and Legal Culture, 2025)
This article aims to reconstruct the understanding of Fiqh Mawaris, particularly concerning the position of Ashabul Furudh in Islamic inheritance distribution, and to integrate waqf assets within the context of contemporary wealth distribution. This research employs a qualitative approach using library research methodology. Data were collected from primary sources such as the Qur'an, hadith, and classical fiqh books, as well as secondary sources including indexed scientific journals and contemporary literature on inheritance and waqf law. Analysis was conducted using descriptive-analytical methods with a comparative approach across Islamic legal schools and modern scholars' perspectives. The research finds that: (1) Ashabul Furudh as fixed-share heirs requires re-evaluation within modern socio-economic contexts without disregarding the qath'i provisions of the Qur'an; (2) There are disagreements among scholars regarding the status of distant relatives (dzawil arham) and inheritance distribution methods, with flexibility through lifetime gifts (hibah) and reconciliation (ash-shulh); (3) The integration of waqf within the inheritance framework faces contemporary challenges that can be addressed through istibdal and cash waqf while adhering to the principle of maslahah; (4) Heirs are legally prohibited from taking waqf land and is protected by Law No. 41 of 2004 concerning Waqf. This research provides a comprehensive synthesis between classical Islamic jurisprudence and contemporary needs, offering a practical framework for the application of inheritance and waqf law in Indonesia by integrating perspectives from various legal schools and modern scholars. This research is limited to library research without empirical field studies; thus, it has not examined actual implementation in courts and communities. Future research should include empirical case studies and comparative studies with other Muslim-majority countries.